Gemcitabine and Vinorelbine Combination Chemotherapy in Anthracycline- and Taxane-pretreated Advanced Breast Cancer - Kim, Hye Jin (Korean Cancer Association, 2008)
PURPOSE: Anthracycline and taxanes are effective agents in advanced breast cancer and prolong survival times. Some patients achieve prolongation of life with capecitabine, gemcitabine, or vinorelbine, even after failure of both anthracycline and taxanes. We analyzed the efficacy and toxicity of gemcitabine and vinorelbine combination chemotherapy in anthracycline- and taxane-pretreated advanced breast cancer. MATERIALS AND METHODS: The medical records of anthracycline- and taxane-pretreated metastatic breast cancer patients who received gemcitabine and vinorelbine combination chemotherapy at the Seoul National University Hospital were reviewed. Gemcitabine (1,000 mg/m(2)) and vinorelbine (25 mg/m(2)) were administered intravenously on days 1 and 8 every 3 weeks. RESULTS: Between 2000 and 2006, 57 patients were eligible (median age, 45 years), and the median number of previous chemotherapy regimens was 3 (range, 1~5). The overall response rate was 30% (95% CI, 18.1~41.9), and the disease control rate was 46% (PR, 30%; SD, 16%). The median duration of follow-up was 33.4 months, the median time-to-progression (TTP) was 3.9 months, and the median overall survival was 10.8 months. None of thepatients with patients with anthracycline and taxane primary resistance showed a response and the median TTP for these patients was significantly shorter than that of other patients (1.9 vs. 4.4 months; p=0.018). Although the efficacy was unsatisfactory in patients with both anthracycline and taxane primary resistance, gemcitabine and vinorelbine combination chemotherapy showed comparable efficacy in anthracycline- and/or taxane-sensitive patients and the patients with secondary resistance, even after failure of second-line therapy. Grade 3/4 hematologic toxicities included neutropenia (18.1%) and febrile neutropenia (0.3%), and non-hematologic toxicities were tolerable. CONCLUSION: Gemcitabine and vinorelbine combination chemotherapy in anthracycline- and taxane-pretreated advanced breast cancer was effective and tolerable.